Integration of Transformational and Distributed Leadership in Elementary School Management: A Strategy to Enhance Teacher Performance and School Achievement - Usman, Usman; Asri B, M. (International Journal of Learning and Instruction (IJLI), 2026)
This study aims to analyze the integration of transformational and distributed leadership in elementary school management as a strategic strategy to improve teacher performance and school achievement. The research was conducted at SDN 144 Kabupaten Barru from September to October 2025. Grounded in the need for adaptive and collaborative leadership models in elementary education, this study employed a quantitative approach with an explanatory survey design. The participants consisted of 124 teachers selected through proportional random sampling. Data were collected using validated questionnaires (Cronbach’s Alpha = 0.91) and analyzed using multiple regression analysis. The results indicate that transformational leadership has a positive and significant effect on teacher performance (β = 0.42, p < 0.001), while distributed leadership also shows a significant effect (β = 0.37, p < 0.001). Simultaneously, both variables significantly influence teacher performance (F = 58.76, p < 0.001) with a coefficient of determination (R²) of 0.63, indicating that 63% of the variance in teacher performance is explained by the integrated leadership model. Furthermore, teacher performance significantly affects school achievement (β = 0.55, p < 0.001). These findings confirm that integrating transformational and distributed leadership substantially enhances teacher performance and contributes to improved school achievement in elementary education.